AB0498 Transient improvement of severe and rapidly progressive dysphagia with autologous peripheral blood hematopoietic stem cell transplantation in a patient with long standing dermatomyositis refractory to standard therapy. (23rd January 2014) - Milanetti, F.; Porrini, R.; Marini, F.; Nisini, R.; Salemi, S.; Lagana, B.; Montefusco, E.; D'amelio, R.
Abstract : Background: Autologous hematopoietic stem cell transplantation (HSCT) has become a significant treatment option for severe autoimmune diseases. Dermatomyositis (DM) and Polymyositis (PM) belong to inflammatory myopathies, autoimmune diseases in which the skeletal muscle is damaged by inflammation and lymphocytic infiltration. Among 6 cases of HSCT on DM/PM reported in the literature, only 1 had no positive effect on the disease course. Age at onset > 40years, dysphasia and dysphagia, severe weakness, failure to induce remission with drugs, chronic-progressive form, male sex and duration of disease >5 years are all considered negative prognostic factors for both mortality and disability [1 ]. Objectives: To manage new-occurrence dysphagia and to stop disease progression in a patient with a high number of negative prognostic factors. Methods: A 58 year-old male patient with a 15-year history of DM refractory to first and second line therapies, including high-dose steroids, methotrexate, azathioprine, cyclophosphamide (Cy), IVIg and Rituximab, came to our observation following worsening of clinical conditions, including new occurrence of severe dysphagia and progressive muscle damage with high serum muscle enzyme levels. Feeding impairment led to Percutaneous Endoscopic Gastrostomy (PEG) tube placement. Thighs MRI showed inflammatory oedema and high amount of atrophy, while muscle biopsy revealed fibre degeneration with CD4+ lymphocyte infiltrate. Thus, HSCT was proposed as a rescue therapy for this patient with several DM negative prognostic factors. During mobilization with Cy and G-CSF, mediastinitis occurred, leading to transplant delay. The patient eventually received autologous T-cell-depleted HSCT after low-dose myeloablative conditioning with Cy and Thiotepa with no grade 3-4 toxicities. Results: Soon after HSCT, dysphagia disappeared and PEG could be removed for 18 months. Twelve months after HSCT, inflammatory oedema on MRI resolved and muscle enzymes normalized. Flow-cytometric study showed naïve and regulatory T cell increase and memory T cell and NK reduction, assessing immunological reset after transplantation. However, arm muscle strength worsened and the patient is still wheelchair bound. Conclusions: HSCT seems to work on still active inflammatory conditions, but it seems less effective when degeneration and cumulative damage predominate. In fact, HSCT in this case was effective on dysphagia, even though only transiently, likely due to recent inflammatory involvement of pharyngeal muscles. References: Snowden JA, Saccardi R, Allez M, Ardizzone S, Arnold R, Cervera R, Denton C, Hawkey C, Labopin M, Mancardi G, Martin R, Moore JJ, Passweg J, Peters C, Rabusin M, Rovira M, van Laar JM, Farge D; EBMT Autoimmune Disease Working Party (ADWP); Paediatric Diseases Working Party (PDWP). Haematopoietic SCT in severe autoimmune diseases: updated guidelines of the European Group for Blood and Marrow Transplantation. Bone Marrow Transplant. 2012 Jun;47(6):770-90. Disclosure of Interest: None Declared